PENGARUH KREDIBILITAS INFLUENCER @DOKTERDETEKTIF DAN CONSUMER TRUST TERHADAP KEPUTUSAN PEMBELIAN HANASUI TIKTOKSHOP SURABAYA - Risma Pebri Anjani; Dicky Surya Putra Pradana; Rafli; Achmad Hafiz Choirul Fanani Firdaus (UNIVERSITAS PGRI MADIUN, 2025)
The purpose of this study is to determine the effect of the credibility of the influencer @Dokterdetektif and consumer trust on purchasing decisions for the Hanasui Bright Expert Serum product through the TikTokshop platform in Surabaya. This study was conducted by applying quantitative research methods and the sample of this study amounted to 100 respondents. The data collection technique in this study used a questionnaire. While the data analysis technique used the classical assumption test and hypothesis test consisting of the t test and f test. The results of this study indicate that there is a significant influence between the credibility variables of the influencer @Dokterdetektif on purchasing decisions for the Hanasui Bright Expert Serum product through the TikTokshop platform in Surabaya. Likewise with the f test which shows that the credibility variables of the influencer @doterdetektif and consumer trust have a significant effect simultaneously on purchasing decisions for the Hanasui Bright Expert Serum product through the TikTokshop platform in Surabaya.